2012
DOI: 10.1089/scd.2012.0060
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Based Tumor-Targeted Gene Therapy in Gastrointestinal Cancer

Abstract: Mesenchymal stem (or stromal) cells (MSCs) are nonhematopoietic progenitor cells that can be obtained from bone marrow aspirates or adipose tissue, expanded and genetically modified in vitro, and then used for cancer therapeutic strategies in vivo. Here, we review available data regarding the application of MSC-based tumortargeted therapy in gastrointestinal cancer, provide an overview of the general history of MSC-based gene therapy in cancer research, and discuss potential problems associated with the utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 81 publications
(105 reference statements)
1
31
0
4
Order By: Relevance
“…Interestingly, in most human tumors, IDO is believed to be expressed continuously 40 , which may explain why tryptophan catabolism is elevated in cancer patients. Since a tumor can be considered to be a wound that never heals, tissue damage signals result in continuous recruitment of MSCs into the tumor 4142 . Using our inducible IDO-transfected mouse MSCs in tumor models, we observed that the ongoing inflammatory microenvironment also induces the expression of IDO, leading to its immunomodulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in most human tumors, IDO is believed to be expressed continuously 40 , which may explain why tryptophan catabolism is elevated in cancer patients. Since a tumor can be considered to be a wound that never heals, tissue damage signals result in continuous recruitment of MSCs into the tumor 4142 . Using our inducible IDO-transfected mouse MSCs in tumor models, we observed that the ongoing inflammatory microenvironment also induces the expression of IDO, leading to its immunomodulatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…They also exhibit a natural tendency of homing into tumors -ability that is starting to be exploited in anticancer treatment, using these versatile cells as cargo delivery for cytotoxic drugs or gene therapy [109]. This behavior has been also reported in pancreatic cancer, by the use of genetically engineered labeled MSCs that efficiently accumulatewithin the pancreatic tumor, when injected into tumor-bearing mice [110].…”
Section: B Mesenchymal Stem Cells -Dual Facets In Cancermentioning
confidence: 89%
“…Surgical resection is the main treatment method for lung cancer, but most patients are diagnosed at the advanced disease stage, when relatively ineffective drug therapy is the only feasible treatment [2]. Mesenchymal stem cells (MSCs) are non-hematopoietic progenitor cells that can be obtained from bone marrow aspirates or adipose tissue, and then expanded and genetically modified in vitro, presenting a potential therapeutic strategy for cancer patients [3]. The molecular mechanisms behind the function of MSCs in tumorigenesis and cancer development are not well-defined, but better knowledge of these mechanisms could facilitated improved prognosis and suppressed malignancy.…”
Section: Introductionmentioning
confidence: 99%